2018
DOI: 10.3390/ijerph15102160
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Ambient Air Pollution on Hospitalization for Respiratory Disease in Taiyuan, China: A Time-Series Analysis

Abstract: In this study, we estimated the short-term effects of ambient air pollution on respiratory disease hospitalization in Taiyuan, China. Daily data of respiratory disease hospitalization, daily concentration of ambient air pollutants and meteorological factors from 1 October 2014 to 30 September 2017 in Taiyuan were included in our study. We conducted a time-series study design and applied a generalized additive model to evaluate the association between every 10-μg/m3 increment of air pollutants and percent incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 34 publications
4
48
3
3
Order By: Relevance
“…Clinical epidemiological evidence has demonstrated that symptoms of chronic bronchitis and abnormal pulmonary function are closely related to exposure to PM2.5 [35,36]. Both short-term and long-term exposure to PM2.5 can directly lead to an increase in the incidence of respiratory diseases, clinical consultation rates, and hospitalization rates [37][38][39]. The microorganisms carried by PM2.5 induce the pro-inflammatory response of resident immune cells, increase intestinal permeability, and change the lumen environment of the intestine, leading to growth of specific microbial strains better suited for survival in an inflammatory environment.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical epidemiological evidence has demonstrated that symptoms of chronic bronchitis and abnormal pulmonary function are closely related to exposure to PM2.5 [35,36]. Both short-term and long-term exposure to PM2.5 can directly lead to an increase in the incidence of respiratory diseases, clinical consultation rates, and hospitalization rates [37][38][39]. The microorganisms carried by PM2.5 induce the pro-inflammatory response of resident immune cells, increase intestinal permeability, and change the lumen environment of the intestine, leading to growth of specific microbial strains better suited for survival in an inflammatory environment.…”
Section: Discussionmentioning
confidence: 99%
“…Taiyuan, is a typical heavy industry city characterized by coal-burning pollution, mainly comes from the exhaust emissions of the heavy industries and coalred heating in winter [5]. With the rapid development of urbanization, motor vehicle exhaust emissions have become one of the main sources of air pollution in Taiyuan city [23].…”
Section: Discussionmentioning
confidence: 99%
“…Air pollutant is a complex mixture of gaseous components, solid and liquid suspended particles in the air [1], mainly includes particulate matter ≤ 10 µm in aerodynamic diameter (PM 10 ), particulate matter ≤ 2.5 µm in aerodynamic diameter (PM 2.5 ), sulfur dioxide (SO 2 ), carbon monoxide (CO), nitrogen dioxide (NO 2 ) and ozone (O 3 ). Several studies have shown that air pollution has a variety of negative effects on human health, such as cardiovascular diseases [2,3], respiratory diseases [4,5], type 2 diabetes mellitus [6], mental disease [7,8], and so on. In recent years, more evidences showed that there was a correlation between ambient air pollution and human reproductive outcomes, such as infertility, preeclampsia, miscarriage and preterm delivery [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical epidemiological evidence has demonstrated that symptoms of chronic bronchitis and abnormal pulmonary function are closely related to exposure to PM2.5 [24,25]. Both short-term and long-term exposure to PM2.5 can directly lead to an increase in the incidence of respiratory diseases, clinical consultation rates, and hospitalization rates [26][27][28]. The microorganisms carried by PM2.5 induce the pro-inflammatory response of resident immune cells, increase intestinal permeability, and change the lumen environment of the intestine, leading to growth of specific microbial strains better suited for survival in an inflammatory environment.…”
Section: Discussionmentioning
confidence: 99%